IN VITRO EVALUATION OF THE ANTIBACTERIAL POTENTIAL OF PSIDIUM GUAJAVA LEAF EXTRACT AGAINST ESCHERICHIA COLI: UNCOVERING THE ROLE OF PHYTOCHEMICAL COMPOUNDS. - Khosasi, Felix; Adella, Cut Adeya; Faradina, Dwi; Lubis, Lokot Donna; Elbert, Elbert (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Introduction: Urinary tract infections (UTIs) are prevalent among women and are commonly caused by Escherichia coli. Although antibiotics are effective, their misuse contributes to rising antimicrobial resistance. Psidium guajava L., a traditional Indonesian medicinal plant, has shown promise as an alternative antibacterial agent. This study aimed to evaluate the inhibitory effect of P. guajava leaf extract against E. coli. Methods: Antibacterial activity was assessed using the agar diffusion method with E. coli ATCC 25922. Ethanolic extracts were obtained by maceration. Six treatment groups, including various concentrations of levofloxacin and dimethyl sulfoxide (DMSO), were tested to compare antibacterial effects. Results: Phytochemical screening revealed the presence of flavonoids, alkaloids, and tannins—compounds known for their antimicrobial activity. Inhibition zone diameters were measured and analysed using the Kruskal–Wallis one-way ANOVA. Discussion: The guava leaf extract demonstrated inhibitory activity against E. coli, likely due to its bioactive compounds. These constituents may exert antibacterial effects through disruption of nucleic acid synthesis, interference with membrane integrity, inhibition of energy metabolism, and prevention of biofilm formation. Conclusion: The ethanolic extract of Psidium guajava leaves exhibits significant antibacterial activity against Escherichia coli.